2017
DOI: 10.1038/ncb3574
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Notch signalling limits angiogenesis via control of artery formation

Abstract: Angiogenic sprouting needs to be tightly controlled. It has been suggested that the Notch ligand dll4 expressed in leading tip cells restricts angiogenesis by activating Notch signalling in trailing stalk cells. Here, we show using live imaging in zebrafish that activation of Notch signalling is rather required in tip cells. Notch activation initially triggers expression of the chemokine receptor cxcr4a. This allows for proper tip cell migration and connection to the pre-existing arterial circulation, ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 70 publications
4
121
3
Order By: Relevance
“…By using time‐lapse imaging, a recent study by Hasan et al . indicated that DLL4 expression preceded Notch pathway activation in leading tip and subsequently in stalk cells (43). Furthermore, expression of DLL4 was also detected in the artery cells (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using time‐lapse imaging, a recent study by Hasan et al . indicated that DLL4 expression preceded Notch pathway activation in leading tip and subsequently in stalk cells (43). Furthermore, expression of DLL4 was also detected in the artery cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…indicated that DLL4 expression preceded Notch pathway activation in leading tip and subsequently in stalk cells (43). Furthermore, expression of DLL4 was also detected in the artery cells (43). Thereby, it is possible that some of the DLL4‐positive cells we observed could be stalk cells and artery cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, it would be interesting to address notch activity in a flow related context, similarly to what is currently being done with Nf-kb, Klf2a, and other flow responsive pathways (Feaver et al, 2013). This assumption is particularly interesting in the context of sprouting angiogenesis and other aspects of angiogenesis where Notch is broadly required (Choi et al, 2017;Hasan et al, 2017;Pitulescu et al, 2017;Tammela et al, 2011). We further show that the expression of Fibronectin1 and Elastinb in the smooth muscle cells surrounding the OFT is not altered in the klf2a -/mutants.…”
Section: Klf2a Modulates Notch Signaling Specifically In the Oft Endomentioning
confidence: 99%
“…These new studies favor an alternative model in which tip cells derive from a clonal population, with asymmetric division transferring high vegfr2 mRNA and VEGFA responsiveness to just one of two daughter cells, rendering the second daughter a stalk cell to maintain the leader-follower hierarchy [37, 39]. In this model, cell-autonomous DLL4 is dispensable for tip cell specification or maintenance, and Notch signaling in tip cells induces CXCR4 expression to set arterial fate and/or allow tip cell-mediated sprout fusion with pre-existing arterial vessels [38, 39]. Venous angiogenic sprouting is less well characterized than arterial sprouting but may involve VEGFC/VEGFR3 and/or bone morphogenetic protein (BMP) signaling, depending on the vascular bed [4042].…”
Section: A Brief Primer On Vascular Developmentmentioning
confidence: 99%